2009
DOI: 10.1016/j.jana.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Actual Condom Use Among Adolescents in Thailand

Abstract: This study examined the relationships among attitudes toward condom use, personal characteristics, condom use self-efficacy, and actual condom use among Thai adolescents. Predictors of condom use were also investigated. Bandura's self-efficacy model for safer sexual behavior provided the theoretical framework for this descriptive correlational design. The sample consisted of 270 Thai vocational students aged 18 to 21 years. Multiple regressions were used to estimate the correlates between the independent study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
4
18
0
1
Order By: Relevance
“…82% claimed full control on whether they took up HPV vaccines ( Table 3 ). We found the high percentage of perceived self-efficacy encouraging because self-efficacy is a strong predictor of vaccination intentions and uptake [ 42 ]. When an individual has high self-efficacy on matters of health behaviors, they may be more easily influenced by health information [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…82% claimed full control on whether they took up HPV vaccines ( Table 3 ). We found the high percentage of perceived self-efficacy encouraging because self-efficacy is a strong predictor of vaccination intentions and uptake [ 42 ]. When an individual has high self-efficacy on matters of health behaviors, they may be more easily influenced by health information [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, while Sriputphong's (2006) national survey of secondary school students found six per cent and nine per cent of females aged 14–16 and 17+, respectively, had ever had intercourse, and O-Prasertsawat and Petchum (2004) produced similar results for a Bangkok secondary school sample, recent studies of vocational/technical students (e.g. Khumsaen & Gary 2009; Rasamimari et al 2007; Rathnawardana Guruge 2004; Thato et al 2003) have yielded much higher levels of female coital experience, both absolutely and as proportions of male levels. Perhaps the most notable study, because it used audio-computer-assisted self-interviewing to assure confidentiality, was one of 1725 15–21-year-olds at three vocational schools in Chiang Rai in 1999 (Liu et al 2006; Manopaiboon et al 2003a; Manopaiboon et al 2003b; van Griensven et al 2001).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, research has shown that perceived normative support and perceived peer behavior are strong determinants of intention to use and actual use of contraceptives (Gayen, and Raeside 2010; Ryan, Franzetta and Manlove 2007; Samandari, Speizer, and O’Connell 2010). Other studies have found that positive attitudes towards contraception increase the likelihood of using a method (Bryant 2009; Khumsaen and Gary 2009; Potard et al 2012). In contrast, negative attitudes such as fear of side effects or perceived disadvantages of contraceptive use have been linked with lack of intention to use and lower use (Bajwa et al 2012; Bosompra 2001).…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, negative attitudes such as fear of side effects or perceived disadvantages of contraceptive use have been linked with lack of intention to use and lower use (Bajwa et al 2012; Bosompra 2001). A high level of perceived self-efficacy (or confidence in one’s ability to act) for contraceptive use has been positively associated with intention to use, increased likelihood of contraceptive adoption, and sustained use (Agha 2010; Bogale, Boer and Seydel 2010; Khumsaen and Gary 2009; Ryan, Franzetta and Manlove 2007; Taffa et al 2002). In analyses that have created an index of ideation, it has been found that higher levels of ideation have been shown to be associated with increased contraceptive use in the literature (Amouzou and Becker 2009; Babalola and Vondrasek 2005; Kincaid 2000a, b).…”
Section: Introductionmentioning
confidence: 99%